Putri Hijau Kearifan Lokal Masyarakat Melayu Sebagai Materi Pembelajaran BIPA - Deliani, Susy; Zulkarnain, Iskandar; Harahap, Muhammad Haekal; Zahara, Siti Fatimah (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The Green Princess